Does institutional quality reduce the impact of market concentration on bank stability? Evidence of developing countries - Hai-Tuan Nguyen (Cogent Economics & Finance, 2023)
This study investigates how market concentration (MC) and institutional quality (IQ) influence bank stability in developing nations, focusing on 80 banks in the ASEAN 4 countries (Indonesia, the Philippines, Malaysia, and Thailand) from 2006 to 2019. The study utilises the generalised method of moments technique to address concerns related to autocorrelation and endogeneity. The findings of the research are noteworthy. Firstly, a positive correlation between bank stability and market concentration is established, supporting the concentration-stability hypothesis. Banks operating in highly concentrated markets tend to exhibit higher stability compared to those in less concentrated markets. However, negative coefficients on square market concentration suggest a potential inverted U-shaped relationship, indicating that market concentration enhances bank stability up to a certain threshold. Secondly, the study highlights the significant impact of institutional quality on bank stability within the ASEAN 4 region. Furthermore, the study found that institutional quality might mitigate the influence of market concentration on bank stability. These results underscore the importance of a well-defined strategy for bank managers and bankers. When market concentration reaches a specific threshold, optimal bank stability is observed, and higher institutional quality contributes to improved bank stability. This research pioneers examining the effects of banking system market concentration and institutional quality on the stability of ASEAN 4 banks.
Keywords: G21; G33; L22; L25; 330; ASEAN 4; bank stability; institution quality; market concentration